A microbial role in the construction of Mono Lake carbonate chimneys?. Issue 5 (9th June 2018) - Brasier, Alexander; Wacey, David; Rogerson, Mike; Guagliardo, Paul; Saunders, Martin; Kellner, Siri; Mercedes‐Martin, Ramon; Prior, Tim; Taylor, Colin; Matthews, Anna; Reijmer, John
Abstract: Lacustrine carbonate chimneys are striking, metre‐scale constructions. If these were bioinfluenced constructions, they could be priority targets in the search for early and extraterrestrial microbial life. However, there are questions over whether such chimneys are built on a geobiological framework or are solely abiotic geomorphological features produced by mixing of lake and spring waters. Here, we use correlative microscopy to show that microbes were living around Pleistocene Mono Lake carbonate chimneys during their growth. A plausible interpretation, in line with some recent works by others on other lacustrine carbonates, is that benthic cyanobacteria and their associated extracellular organic material (EOM) formed tubular biofilms around rising sublacustrine spring vent waters, binding calcium ions and trapping and binding detrital silicate sediment. Decay of these biofilms would locally have increased calcium and carbonate ion activity, inducing calcite precipitation on and around the biofilms. Early manganese carbonate mineralisation was directly associated with cell walls, potentially related to microbial activity though the precise mechanism remains to be elucidated. Much of the calcite crystal growth was likely abiotic, and no strong evidence for either authigenic silicate growth or a clay mineral precursor framework was observed. Nevertheless, it seems likely that the biofilms provided initial sites for calcite nucleation and encouraged the primary organised crystal growth. We suggest that the nano‐, micro‐ and macroscale fabrics of these Pleistocene Mono Lake chimneys were affected by the presence of centimetre‐thick tubular and vertically stacked calcifying microbial mats. Such carbonate chimneys represent a promising macroscale target in the exploration for ancient or extraterrestrial life.